ADVANCED EXPERIENCE OF PRESCHOOL EDUCATION - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the advanced experience of preschool education and education in foreign countries is studied on the basis of a comparative analysis. Data on the forms and conditions of preschool education in mainly developed Western and Eastern countries are presented. The content of the reforms carried out in the field of preschool education and training in our country and the views on its effectiveness are also reflected.